KEEFEKTIVITASAN PENERAPAN STRATEGI PEMBELAJARAN EKSPOSITORI PADA MATA PELAJARAN MEKANIKA TEKNIK - Aldi Restu Putra (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
This study aims to examine the results of optimizing the application of expository learning strategies in Engineering mechanics courses. The research data is obtained from the analysis of relevant articles related to the discussion of the application of expository learning strategies in Engineering mechanics courses. The research method uses a literature review that involves studying, observing, and critically evaluating previous research sources on the topic. The research results are written using a qualitative descriptive approach. Studies conducted on many previous studies show that the application of this expository learning strategy is very optimal and effective in Engineering mechanics courses.